Early postnatal changes of circulating N-terminal-pro-B-type natriuretic peptide in neonates with congenital diaphragmatic hernia. (July 2020) - Heindel, Katrin; Holdenrieder, Stefan; Patel, Neil; Bartmann, Peter; Schroeder, Lukas; Berg, Christoph; Merz, Waltraut Maria; Mueller, Andreas; Kipfmueller, Florian
Abstract: Background: Severity of lung hypoplasia, pulmonary hypertension (PH) and cardiac dysfunction are major contributors to mortality in congenital diaphragmatic hernia (CDH). Therefore, early assessment and management is important to improve outcome. NT-proBNP is an established cardiac biomarker with only limited data for early postnatal risk assessment in CDH newborns. Aims: To investigate the correlation of NT-proBNP at birth, 6 h, 12 h, 24 h, and 48 h with PH and cardiac dysfunction and the prognostic information of NT-proBNP for the use of ECMO support or mortality. Subjects: 44 CDH newborns treated at our institution (December 2014–October 2017) were prospectively enrolled. Outcome measures: Primary clinical endpoint was either need for ECMO or death within the first 48 h (group A). Infants not receiving ECMO support were allocated to group B. Mortality was tested as secondary endpoint. Results: NT-proBNP levels measured at 6 h, 12 h, 24 h and 48 h postpartum correlated significantly with PH severity following NICU admission and at 24 h, and with severity of cardiac dysfunction at birth, 24 h, 48 h and after 7 days of life. There was no difference in NT-proBNP levels between survivors and non-survivors. NT-proBNP levels were significantly higher in group A at 6 h (p = 0.007), 12 h (p = 0.036), and 24 h (p = 0.007), but not at birth (p = 0.785) or 48 h (p = 0.15) compared to group B. Conclusion: NT-proBNP analysis in the first 48 h of life may be useful to assess PH and cardiac dysfunction in CDH newborns and to predict the need for ECMO support. Highlights: Cardiac dysfunction is an indicator for clinical outcome in CDH newborns. NT-proBNP within the first 48 h correlated significantly with cardiac dysfunction and PH severity on echocardiography. NT-proBNP measurement during first DOL might allow for a short-term prognosis. Fixed collection times are needed due to intraindividual changes in NT-proBNP-levels.